2011
DOI: 10.1016/j.jcrs.2011.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis after cataract surgery in China, 1995–2009

Abstract: A systematic search of the China National Knowledge Infrastructure database for articles on endophthalmitis after cataract surgery between 1995 and 2009 identified 57 articles that included 403 eyes. The incidence of endophthalmitis after cataract surgery was 0.06% (140/233,115). Treatments included intraocular antibiotic injection in 54.1% of eyes and immediate vitrectomy in 40.2%. Of 356 intraocular samples, 214 (60.1%) were culture positive; 187 (87.3%) bacterial and 27 (12.7%) fungal. The presenting visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 8 publications
2
39
1
4
Order By: Relevance
“…There are broad gaps in technology among different districts and different level hospitals in China. Based on a literature-based retrospective analysis, Sheng et al reported an incidence of endophthalmitis after cataract surgery in China between 1995 and 2009 of 0.06% (range 0.02–0.4%) 9. However, 10 of the 17 studies to which Sheng referred described cataract surgery as it was practiced before 2003 and these studies represented 80% of Sheng's retrospective analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are broad gaps in technology among different districts and different level hospitals in China. Based on a literature-based retrospective analysis, Sheng et al reported an incidence of endophthalmitis after cataract surgery in China between 1995 and 2009 of 0.06% (range 0.02–0.4%) 9. However, 10 of the 17 studies to which Sheng referred described cataract surgery as it was practiced before 2003 and these studies represented 80% of Sheng's retrospective analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies in other countries, incidence of endophthalmitis after cataract surgery ranged from 0.02% to 0.3% 1–8. In China, some small-scale and single-centre investigations showed an incidence ranging from 0.02% to 0.4% 9. Due to political and economic factors, there is a huge gap in the levels of medical care provided among different districts and different hospitals here.…”
Section: Introductionmentioning
confidence: 99%
“…This rate is comparable to or better than other studies of endophthalmitis following intravitreal therapy and cataract surgery. 15,17,18,21,32,33,[35][36][37] As with endophthalmitis following cataract surgery, vitreous sampling achieved a higher organism yield rate compared with aqueous sampling. 28,32,33 However, as aqueous sampling yielded an organism that was not identified by vitreous sampling in two cases, it may be optimal to perform both vitreous and aqueous sampling in the event of PIAE in order to maximise the chance of identifying a causative pathogen.…”
Section: Microbiologymentioning
confidence: 99%
“…1 The most commonly seen pathogens causing postoperative phacoemulsification endophthalmitis are gram-positive (50.9% to 94.0%), gram-negative (6.0% to 42.0%), and fungal (up to 12.7%) microorganisms. [2][3][4][5][6] Fusarium species, which are filamentous fungi, have been described as the most common cause of fungal keratitis. 7 Qiu et al 8 report that Fusarium solani was the most frequently isolated pathogen in 27 of 61 eyes in which fungal keratitis was diagnosed.…”
Section: Jcrs Online Case Reports 2014; 2:63-67 Q 2014 Ascrs and Escrsmentioning
confidence: 99%